The horizon of pediatric cardiac critical care - Pollak, Uri; Feinstein, Yael; Mannarino, Candace N.; McBride, Mary E.; Mendonca, Malaika; Keizman, Eitan; Mishaly, David; van Leeuwen, Grace; Roeleveld, Peter P.; Koers, Lena; Klugman, Darren (Frontiers in Pediatrics, 2022)
Pediatric Cardiac Critical Care (PCCC) is a challenging discipline where decisions require a high degree of preparation and clinical expertise. In the modern era, outcomes of neonates and children with congenital heart defects have dramatically improved, largely by transformative technologies and an expanding collection of pharmacotherapies. Exponential advances in science and technology are occurring at a breathtaking rate, and applying these advances to the PCCC patient is essential to further advancing the science and practice of the field. In this article, we identified and elaborate on seven key elements within the PCCC that will pave the way for the future.